The Level of Foundational Skills Application Among Graduate Employees in Edo and Delta States, Nigeria - Osahon, M. E.; Adesuwa, Imafidon (Asian Journal of Assessment in Teaching and Learning, 2021)
This study aimed to assess the level of foundational skills of graduate employees in Edo and Delta States using Business Education) graduates as a case study. Three research questions and three hypotheses guided the study. Adescriptive survey research design was adopted for the study. The population was 1,016 supervisors with a sample size of 309 determined by using the proportionate stratified sampling technique. A structuredquestionnaire was used to collect data.  Reliability of the instrument was determined by using Cronbach Alpha reliability method and an overall reliability coefficient of 0.79 was obtained.  Data relating to the research questions wereanalyzed using arithmetic mean and standard deviations.  The t-test was used to test null hypotheses at a 0.05 level of significance.  The study revealed that the supervisors rated application of all the aspects of foundational skills by Business Education graduates to be moderately applied. From the findings, it was concluded that the level of application of foundational skills by Business Education graduates is inadequate to meet the demands of employers. Hence, the training received by graduates is insufficient to meet the challenges of the modern-day office and thereby inferring that graduates from other disciplines do not have the necessary training to meet with the challenges of modern-day office.  Based on the findings of this study, the researcher recommended that the observed deficiencies in literacy and numeracy skills which constitute part of the foundational skills should be adequately addressed by revamping the general studies courses in general studies units in tertiary institutions.